The influence of different preparation methods on the microstructures and properties of the in situ bulk-metallic-glass-matrix composites. Issue 4 (10th February 2015) - Meng, Y.; Sha, P.F.; Zhu, Z.W.; Yu, D.C.; Fu, H.M.; Wang, A.M.; Li, H.; Zhang, H.W.; Zhang, H.F.
Abstract: Abstract : In this work, the effects of different preparation methods on the microstructures and properties of the Ti45.7 Zr33 Ni3 Cu5.8 Be12.5 alloy were systematically studied by both experimental and numerical ways. It is found that the heating methods and the cooling rate during the process of preparation have great influences not only on the morphology and crystalline structure of the solid solutions but also on the thermal stability of the amorphous phase. Furthermore, the different crystalline structures and micromorphologies of the ductile phase will also influence the mechanical properties. And the uniaxial compression tests at room temperature verify that the Ti45.7 Zr33 Ni3 Cu5.8 Be12.5 samples obtained by different preparation methods possess different degrees of plasticity. The better comprehensive properties were found for samples with a larger size under the copper mold cooling conditions. The variation of the morphology of the solid solution phase under different preparation conditions is believed to be the vital factor that leads to the diversity in properties.